Novel Glass‐Ceramic Composition as Sealant for SOFCs. Issue 12 (11th September 2014) - Smeacetto, Federico; De Miranda, Auristela; Chrysanthou, Andreas; Bernardo, Enrico; Secco, Michele; Bindi, Massimiliano; Salvo, Milena; Sabato, Antonio G.; Ferraris, Monica; Wei, W.‐C.
<x xml:space="preserve">Abstract</x> This work deals with the design, the characterization, and testing of a novel glass‐ceramic to be used as sealant for planar solid oxide fuel cells and its compatibility with Mn1.5Co1.5O4‐coated Crofer22APU. Thermal, sintering, and crystallization behavior and thermo mechanical properties of the sealant are reviewed and discussed, indicating therefore that these compositions can be deposited at 850°C and provide an excellent compatibility with both the Mn1.5Co1.5O4‐coated Crofer22APU and the anode‐supported electrolyte. In particular, Mn1.5Co1.5O4‐coated Crofer22APU/sealant/anode‐supported‐electrolyte joined samples have been submitted to thermal tests (in air atmosphere) from RT to 800°C (SOFC operating temperature) up to 500 h. No interactions, cracks formation, or failure were observed at the Mn1.5Co1.5O4‐coated Crofer22APU/sealant interface and between the glass‐ceramic and the anode‐supported‐electrolyte after 500 h of thermal tests in air atmosphere.